2022
DOI: 10.3390/molecules27113477
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Neoastilbin on Monosodium Urate Stimulated THP-1-Derived Macrophages and Gouty Arthritis in Mice through NF-κB and NLRP3 Inflammasome Pathways

Abstract: Gouty arthritis (GA) is a frequent inflammatory disease characterized by pain, swelling, and stiffness of joints. Neoastilbin is a flavonoid isolated from the rhizome of Smilax glabra, which possesses various anti-inflammatory effects. However, the mechanism of neoastilbin in treating GA has not yet been clarified. Thus, this study was to investigate the protective effects of neoastilbin in both monosodium urate (MSU) stimulated THP-1-derived macrophages and the animal model of GA by injecting MSU into the ank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…33,34 Moreover, it was demonstrated that IL-6 induced osteoclast formation. 35 Wenjing Xu et al 36 found that reducing IL-6 secretion through drug intervention could alleviate the symptoms of gout flare.…”
Section: Jak/stat Signaling Pathwaymentioning
confidence: 99%
“…33,34 Moreover, it was demonstrated that IL-6 induced osteoclast formation. 35 Wenjing Xu et al 36 found that reducing IL-6 secretion through drug intervention could alleviate the symptoms of gout flare.…”
Section: Jak/stat Signaling Pathwaymentioning
confidence: 99%
“…We also observed signi cant elevation of serum UA, CRE and BUN levels and reduction of urine UA and CRE levels in model mice. As our data indicated, we successfully induced a model combined hyperuricemia and gouty arthritis in mice by combination of intraperitoneal injection of PO and xanthine and intra-articular injection of MSU crystals [12,13,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…A horizontal line was drawn at 0.5 cm on the ankle of with a fadeless marker as a uni ed standard for measuring the volume of toes before injection. The toe volume was measured before and 2, 4, 6, 20 and 24 h after model establishment with a toe volume measuring device [12,13]. The obtained data were calculated according to the following formula.…”
Section: Measurement Of Ankle Joint Swellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, neoastilbin significantly ameliorated swelling degree and histopathological injury in ankle joints of MSU-induced GA mice. In addition, neoastilbin markedly diminished the secretion of IL-1β, IL-6 and TNF-α and repressed the activation of NF-κB and NLRP3 inflammasome pathways in vivo and vitro ( 84 ). Tetrahydropalmatine (THP), the main active component of Corydalis yanhusuo , exhibits excellent anti-inflammatory and analgesic activities.…”
Section: Therapeutic Strategies For Targeting Nlrp3 In Gamentioning
confidence: 99%